Structural response of a fibre reinforced concrete pile-supported flat slab: full-scale test. (15th July 2021) - Aidarov, Stanislav; Mena, Francisco; de la Fuente, Albert
Highlights: SFRC flat slab of the 7c strength class (considering mean values) was tested. SFRC slab demonstrated no loss of structural integrity under the load of 16 kN/m 2 . Constructed SFRC element revealed a suitable cracking and deflection control. The average fibre contribution in the horizontal plane resulted to be 76.8%. An increment of fibre amount from the top to the bottom of the slab was depicted. Abstract: The total substitution of traditional reinforcement in the form of steel bars by fibres can be mainly found in elements with favourable boundary conditions and subjected to low-moderate load levels. However, the rigorous study of fibre reinforced concrete (FRC) and its potential fields of application over the last decades permitted this material to face structural application with greater responsibility in terms of structural integrity and mechanical capacity – construction of FRC flat slabs. This promising technology was used in a dozen buildings with recognition of positive outcomes with respect to the optimization of resources, reduction of execution time, and environmental impacts. Despite these achievements, the application of FRC in flat slabs is still limited in the building sector because of certain concerns of the material capacities, and existence of some aspects related both to service and ultimate limit states, which are still unclear. With this in mind, an extensive experimental programme was carried out and focused on the construction of a full-scale FRC flat slab and its loading protocol in order to analyse both crack and deflection patterns. Likewise, the structure was led to failure, which also allowed assessing both the bearing and deformability capacities as well as the fibre distribution and orientation. The results derived from this experimental program are expected to increase the confidence of designers and practitioners on the use of FRC as structural material for column-supported flat slabs.